Działania Rzecznika Praw Obywatelskich w zakresie problematyki osób zaginionych - Wentkowska, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Based on the motions submitted for the attention of the Commissioner for Human Rights, as well as on the inspected cases, this article discusses the system of searching for missing persons. The Police implemented and continuously improve the system of searching for missing persons. However, the procedures are often imperfect. Some-times it results in a situation that search procedures are too late, especially in cases in which time is a crucial factor. Hence the question arises as to whether the legal and logistic aspects of searching for missing persons in Poland is well organized. Another question is whether the rules governing search operations are clear and understandable for all the services. To ensure efficient rescue operations undertaken by the services responsible for the maintenance of order and safety in the search for missing persons, the Commissioner for Human Rights asked the Minister of the Interior to take the need for an introduction of some legislative changes into consideration.
Keywords: Rzecznik Praw Człowieka w Polsce; osoby zaginione; Policja; SAR (poszukiwanie i ratownictwo)